Measurement of flanking transmission for the characterisation and classification of cross laminated timber junctions. (1st December 2018) - Morandi, F.; De Cesaris, S.; Garai, M.; Barbaresi, L.
Highlights: A measurement campaign on flanking transmission on CLT junctions is presented. There is a strong dependence of the Kij of the connection system. The use of resilient interlayers is effective starting from 400 Hz. The formulae of ISO 12354 do not match with experimental data at low frequencies. The damping of CLT is discussed in relation to the classification of the junctions. Abstract: The acoustic modelling of timber constructions is a major concern since wood construction technology has started to tackle multi-storey buildings. The recent update of the EN ISO 12354:2017 package of standards introduced indications relative to lightweight timber structures and a distinction between CLT and frame buildings that is related to the different characterisation of flanking transmissions. Within this framework, this work presents the results of a measurement campaign conducted on CLT junctions to study the influence of the connection on the vibration reduction indices. The investigation regards the influence of the kind and number of connectors, the hierarchy of the transmission paths and the use of the resilient interlayers. The experimental data show that the transmission of vibrations between CLT panels is strongly related to the metallic connectors that characterise the junction. The analysis on the damping of CLT panels suggests that the reverberation time does not strictly depend on the adjacent elements; a comparison between the loss factor normalised data and the geometry normalised data is finally proposed.